Penerapan Denda oleh Pemerintah Kabupaten Gianyar Kepada Masyarakat Pelanggar Protokol Kesehatan Selama Masa Pandemi Covid-19 - A.A. Tri Padmawati; Ida Ayu Putu Widiati; Luh Putu Suryani (Jurnal Analogi Hukum, 2021)
Covid-19 is a dangerous epidemic that attacks the entire community with the rapid transmission. Health protocols are mandatory for all parties to carry out safe activities during the Covid-19 pandemic. Such as Gianyar Regent Regulation No. 56 of 2020 which discusses health protocols. Problems in this study are: (1) How is the regulation of the imposition of fines on people who violate health protocols during the Covid-19 pandemic in Gianyar Regency? (2) How is the imposition of fines on people who violate health protocols during the Covid-19 pandemic in Gianyar Regency?. The method used is empirical research. The data collection technique used was library research, observation, interviews, and literature study. Analysis of the data used descriptive analysis techniques. The legal basis for the imposition of fines is Article 11 of the Gianyar Regent's Regulation no. 56 of 2020. The regulation on the imposition of fines that have been implemented is effective, it can be seen from the decrease in the level of violations from before the regulation was enacted until the regulation was enacted.